There is no magic in the Old Saxon Heliand - Verio Santoro (Filologia Germanica)
Although the Old Saxon poem has been thoroughly investigated for two centuries now, the issue of the possible traces of pre-Christian Germanic magical traditions within it has not been sufficiently investigated. The only study specifically devoted to the (alleged) magical elements in Heliand belongs to G.R. Murphy (1991), whose opinions are in line with the studies already undertaken by the Lutheran theologian A.F.C. Vilmar in 1845, a few years after the publication of J.A. Schmeller’s editio princeps (1830). According to Vilmar, the Old Saxon poem was “das Christentum im deutschen gewande, eingekleidet in die poesie und die sitte eines edlen deutschen stammes”. The purpose of this work is to subject to a careful textual analysis the six passages of the Heliand in which, according to the American scholar – who emphasizes the characteristics of what has now long been a misunderstood, stereotyped and obsolete idea of “Germanism” – Christ’s acting as a sorcerer would be obvious; it will be shown, on the contrary, that the image of Christ resulting from the poem is far removed from that of a sorcerer.